The 10 Rules of Successful Nations - Sharma, Ruchir (UK Penguin Books, 2020)
This short primer distils Ruchir Sharma's decades of global analytic experience into ten rules for identifying nations that are poised to take off or crash. A wake-up call to economists who failed to foresee every recent crisis, including the cataclysm of 2008, 10 Rules is full of insights on signs of political, economic, and social change. Sharma explains, for example, why autocrats are bad for the economy; robots are a blessing, not a curse; and consumer prices don't tell you all you need to know about inflation. He shows how currency crises begin with the flight of knowledgeable locals, not evil foreigners; how debt crises start in private companies, not government; and why the best news for any country is none at all. Rethinking economics as a practical art, 10 Rules is a must-read for business, political and academic leaders who want to understand the most important forces that shape a nation's future.
Include Index
Keywords: Economic forecasting -- Economic history